Besides neuro-imaging, the Thy1-YFP mouse could serve for visualizing experimental tumours, inflammation and wound-healing - Winter, Zoltan; et al. (Scientific Reports, 2014)
The B6.Cg-Tg(Thy1-YFP)16Jrs/J transgenic mouse strain, widely used to study neuronal development and regeneration, expresses the yellow fluorescent protein (YFP) in the peripheral nerves and the central nervous system under the control of regulatory sequences of the Thy1 gene. The Thy1 (CD90) cell surface glycoprotein is present on many cell types besides neurons and is known to be involved in cell adhesion, migration and signal transduction. We hypothesized that Thy1-activating conditions could probably activate the truncated Thy1 regulatory sequences used in the Thy1-YFP construct, resulting in YFP transgene expression outside the nervous system. We demonstrated that the stroma of subcutaneous tumours induced by the injection of 4T1 or MC26 carcinoma cells into BALB/c(Thy1-YFP) mice, carrying the same construct, indeed expressed the YFP transgene. In the tumour mass, the yellow-green fluorescent stromal cells were clearly distinguishable from 4T1 carcinoma cells stably transfected with red fluorescent protein. Local inflammation induced by subcutaneous injection of complete Freund's adjuvant, as well as the experimental wound-healing milieu, also triggered YFP fluorescence in both the BALB/c(Thy1-YFP) and B6.Cg-Tg(Thy1-YFP)16Jrs/J mice, pointing to eventual overlapping pathways of wound-healing, inflammation and tumour growth.<br
Keywords: B6.Cg-Tg(Thy1-YFP)16Jrs/J; CD90; inflammation; wound-healing; tumour growth